2008
DOI: 10.1159/000123615
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Urogenital Sinus with Consecutive Hydrometrocolpos because of Labial Fusion: Prenatal Diagnostic Difficulties and Postpartal Therapeutic Management

Abstract: Objective: To elucidate the differential diagnoses of tumorous dilations in the fetal pelvic region detected by prenatal ultrasound and the postnatal management demonstrated on a fetus with 29 weeks of gestation with a retrovesical located bottle-like cystic structure measuring 54 × 31 × 27 mm within the pelvis. Postnatal findings were a labial fusion and a consecutive hydrometrocolpos due to a urethrovaginal fistula. Method: Case report of a fetus affected by an intricate cloacal anomaly. Results: The long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Ascites was moderate [7], the same findings were confirmed by Gul et al who reported association of UGS, ureterocele, hydroureter, and hydronephrosis [8]. …”
Section: Discussionmentioning
confidence: 54%
“…Ascites was moderate [7], the same findings were confirmed by Gul et al who reported association of UGS, ureterocele, hydroureter, and hydronephrosis [8]. …”
Section: Discussionmentioning
confidence: 54%
“…The knowledge of the molecular basis of the disease in this family in turn allows prenatal diagnosis by chorionic villous sampling or by amniocentesis. Our case highlights the inclusion of AIS in the differential diagnosis of pregnancies that show a sex discordance between ultrasonographic gender and karyotype like in other conditions [12] where the final diagnosis cannot be confirmed until after delivery. Molecular analysis of the AR gene is now available in order to confirm the diagnosis.…”
Section: Commentmentioning
confidence: 78%
“…Hydrocolpos is caused by obstruction to vaginal fluid drainage; among the causes described are McKusick-Kaufman syndrome, 5 vaginal or external genitalia malformation such as labial fusion, 6 cloacal anomaly, 7,8 imperforated hymen 9,10 and persistent urogenital sinus. 11,12 Cases of persistent urogenital sinus or cloacal syndromes (depending on the moment of arrest of embryonic development) like the present one are sporadic while McKusick-Kaufmann syndrome is autosomal recessive and have cardiac defects and polydactyly.…”
Section: Discussionmentioning
confidence: 99%